English Speakers Learning Spanish: Perception Issues Regarding Vowels and Stress - Romanelli, Sofía (2015)
The present pilot study examines both the perception of Spanish vowels /a, e, o/ in word – final position and the perception of final and penultimate stress of words ending in those vowels by beginner American English learners of Spanish. Seventeen English speakers and seven native Spanish speakers participated in this study. The English speakers were exposed to 90 hours of Spanish lessons during a three–week course in Mar del Plata, Argentina, a Spanish speaking country. Participants’ perception was assessed by pretest and posttest, which consisted of identification tasks with nonce words. The study yielded these results: (a) native English-speaking participants perceived Spanish vowels like native Spanish-speaking participants after a three-week language course; (b) Initially, English speakers received lower scores in the perception of stress than did Spanish speakers who served as a comparison (control) group; c) Three weeks after exposure to the language, the English speaking students performed like Spanish speakers in the perception of penultimate stress but not in the perception of final stress. The article concludes that vowel perception is not a problem for English speakers learning Spanish while the perception of stress contrasts is a difficult challenge. More emphasis should be given to stress perception in Spanish programs for English speakers, as stress contrasts, together with vowels, are key to interpreting the meaning of a verb in the Spanish verbal morphology system.